MUTU FISIK DAN MIKROBIOLOGI DAGING SAPI ASAL RUMAH POTONG HEWAN (RPH) KOTA PEKANBARU - Bambang Kuntoro; Rarah Ratih Adjie Maheswari; Heni Nuraini (State Islamic University of Sultan Syarif Kasim Riau, 2013)
Meat is a food from animal that have a high nutrient contents (water, protein, fat, vitamins and minerals). This food is very perishable, because its has enough elements of good nutrition. The nutrient content of meat makes a very suitable medium for the growth of microorganisms, especially bacteria. The presence of bacterial contamination in meat will impact on the meat quality of physical and microbiological. This study aimed to determine the physical and microbiological quality of beef carcass and meat from the slaughterhouse in Pekanbaru and compared with the Indonesian National Standard (INS) No. 3932: 2008 on carcass and meat quality of beef. The results showed that the pH of beef muscle Longissimus Dorsi et lumbarum (LD) is at 5:37, while the Biceps Femoris (BF) is 5.56. Meat color values in LD muscle have a score of 6 (red light), while the flesh BF has a score of 7 (red is a bit darker). While the value of the percentage of free water in LD muscle is 61.80% higher than the BF muscle is 53.53%. Microbiological analysis of the microbial contamination Total Plate Count (TPC), Eschericia coli and Coliform in fresh meat from slaughterhouses inPekanbaru city is above the maximum threshold according to INS 3932: 2008, but negative for Salmonella contamination. The conclusion of this study that physical (pH, color, and percentage of free water) origin beef slaughterhouses in Pekanbaru city still has a good quality and are in the normal range of fresh meat. But in terms of microbiological contamination, especially bacteria TPC, E. coli and coliform were above standard.